Early diagnosis and treatment of Ramsay Hunt syndrome: a case report - Chen Yu; Haw-Yu Lee; Yen-Chia Chen (International Journal of Emergency Medicine)
Abstract Background Ramsay Hunt syndrome (RHS), a rare complication of varicella-zoster virus (VZV) reactivation, presents with ipsilateral facial paralysis, ear pain, and vesicular rash. Early recognition is crucial for prompt treatment and optimal outcomes. Case presentation We report a case of a 67-year-old woman with RHS who presented with right-sided facial palsy, severe ear pain, and fluid-filled blisters. Prompt diagnosis and initiation of antiviral and glucocorticoid therapy led to significant symptom improvement. Conclusions Healthcare providers should consider RHS in patients with facial palsy, especially when accompanied by ear pain and vesicular rash, to facilitate early intervention and prevent long-term complications.